The role of external examining in higher education : challenges and best practices - Sengupta, Enakshi; Blessinger, Patrick; Ssemwanga, Andrew; Cozza, Barbara (Emerald Publishing Limited, 2021)
Using an external examiner in an institution is not a new phenomenon. Whilst there is no 'one size fits all' approach, how can researchers collaborate on key developments in maintaining higher education standards in order to overcome challenges and cultivate best practice together? This book considers the external examination challenges and best practice examples in academia in various parts of the world. With several chapters that cover examples of mitigating disadvantage and creating opportunities without compromising the quality assurance process, the authors examine how universities are engaged in safeguarding procedures at the same time as enhancing the quality standards. Providing a comprehensive international focus, this volumes showcases how we might make external examining a rigorous process which is fair, reliable and consistent across the globe.
Includes index.
Keywords: Universities and colleges -- Examinations.; Education, Higher -- Evaluation.; Quality assurance.; Education -- Higher.; Higher & further education, tertiary education.; elektronické knihy; electronic books